131k views
3 votes
I need help with this question

I need help with this question-example-1

2 Answers

3 votes

3rd one for the answer all the other ones are wrong. It shifted down

User Totoro
by
6.4k points
3 votes

ANSWER


y = \sqrt[3]{x + 4} - 1

Step-by-step explanation

The given function is


y = \sqrt[3]{x}

The transformation


y = \sqrt[3]{x + k} - c

shifts the graph of the base function k units left and c units down.

Since the graph is shifted 4 units left, k= 4

Also, the graph is shifted 1 unit down.

This implies that c=1

The new equation is


y = \sqrt[3]{x + 4} - 1

The last option is correct.

User Tiffini
by
5.1k points